Developing a Marketing Strategy to Improve Occupancy Performance: A Case Study of Atmosfera De Lembang Villa - Nathanael, Gabriel Adiv; Wandebori, Harimukti (Riviera Publishing, 2026)
This research aims to develop an integrated marketing strategy to improve the declining occupancy performance of Atmosfera de Lembang, a premium private villa in West Bandung, Indonesia. Despite offering superior facilities and achieving consistently high guest satisfaction scores, the villa experienced a 39% decrease in occupancy between 2022 and 2024. Using a mixed-method, single-case study design, the research combines qualitative interviews, quantitative surveys, digital performance audits, and strategic marketing analyses (PESTEL, Porter’s Five Forces, VRIO, Value Chain, STP, SWOT–TOWS, and the 7Ps). Findings reveal that strong product quality is overshadowed by low brand awareness, weak digital visibility, unstructured marketing activities, and insufficient OTA optimization, resulting in a significant awareness–performance gap. Market segmentation identified three clusters, with “Premium Comfort Families” emerging as the ideal target segment, aligned with the villa’s value proposition of “Luxury That Feels Like Home.” The study proposes a 12-month phased marketing strategy covering brand revitalization, multi-platform distribution, influencer collaborations, digital advertising, customer retention programs, and pricing optimization. The strategy is projected to increase monthly bookings from 4–5 to 15–17, elevate annual revenue to IDR 960M–1.08B, deliver a 239–357% ROI, and achieve breakeven within 5–7 months. The results highlight the importance of structured, data-driven marketing for sustaining competitiveness in oversaturated hospitality markets.